UPAYA MEMELIHARA SOLIDARITAS MEKANIK PADA ETNIS MADURA DI KELURAHAN PAL LIMA KECAMATAN PONTIANAK BARAT - Jannah, Nurul; Bahari, Yohanes; Zakso, Amrazi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe various cultural traditions inherent in the Madurese ethnic community in RW 008 became one of the factors driving the maintenance of mechanical solidarity between them, even the conflicts arising from the Carok culture were not enough to weaken the bonds between them. It is not easy to perpetuate solidarity in the life of a multiethnic society, especially the flow of modernization that is also felt by the community. Various efforts were made such as maintaining traditions, networks or social relations, and religious ties to maintain their solidarity. This research is included in the type of field research. The method used is descriptive qualitative. Sources of data are the RT head and Madurese ethnic in RW 008, Pal Lima Subdistrict, Pontianak Barat District. Data collection techniques used were observation, interviews, and documentation. Data analysis techniques are data reduction, data presentation and conclusion drawing / verification. The results of the study in this study that mechanical solidarity in ethnic Madurese is still well maintained through three elements, namely maintaining tradition, family ties or kinship, and religious tiesKeywords:Mechanical Solidarity, Ethnic Madura